2017
DOI: 10.1002/app.45462
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and morphological properties of microinjection molded polypropylene/carbon nanocomposites

Abstract: A series of different carbon (carbon black, carbon nanotubes, and graphite nanoplatelets) filled polypropylene nanocomposites were prepared by melt blending, then followed by compression molding or microinjection molding (µIM). Direct current electrical conductivity measurements and melt rheology tests were utilized to detect the percolated structure for compression molded polypropylene/carbon nanocomposites. For µIM, a rectangular mold insert which has a three‐step decrease in thickness along the flow directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 46 publications
5
32
0
Order By: Relevance
“…, the percolation threshold ( p c ) for compression‐molded PP/SG composites is about 30 wt% (i.e., 14.8 vol%). However, the p c for microinjection‐molded samples shifted to higher filler concentrations when compared with the samples prepared with compression molding . Abbasi et al reported that the p c for compression‐molded PP/CNT and PC/CNT composites is 1 wt% and 3 wt%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…, the percolation threshold ( p c ) for compression‐molded PP/SG composites is about 30 wt% (i.e., 14.8 vol%). However, the p c for microinjection‐molded samples shifted to higher filler concentrations when compared with the samples prepared with compression molding . Abbasi et al reported that the p c for compression‐molded PP/CNT and PC/CNT composites is 1 wt% and 3 wt%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been carried out regarding the micromolding of unfilled thermoplastics . However, applications that require microparts having specified electrical, thermal, and mechanical properties can be accommodated by using polymeric composites with multifunctional fillers . To date, a few studies have been performed with the μIM of multiwalled carbon nanotube (CNT)‐loaded polymer composites .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To compare the electrical and morphological properties of various other CNT‐filled thermoplastic micromoldings, another set of PP, PS, and polyamide 6 (PA6) masterbatches obtained from the Hyperion Catalysis International Inc was diluted with corresponding pure components. The properties of PP/CNT, PS/CNT, and PA6/CNT masterbatches as well as corresponding pure polymers are available in the previous studies …”
Section: Methodsmentioning
confidence: 99%